Artificial intelligence as an educational media to improve adolescent reproductive health: Research and development studies - Fatiah Handayani; Nurhayati Nurhayati; Ami Kamila (Jurnal Keperawatan Padjadjaran, 2022)
Background: Cognitive accessibility, psychosocial accessibility, and geographic accessibility are all barriers to adolescent sexual and reproductive health services. Cognitive accessibility, as an educational medium, provides access to comprehensive adolescent reproductive health information. This study aimed to turn a textbook into a learning module for adolescent reproductive health using artificial intelligence. Methods: The study used the Borg and Gall Research and Development design. Purposive sampling was used to select the trial sample of students, teachers, and media experts at Muhammadiyah Junior High School 4 Margahayu, Bandung Regency. Interviews, validation sheets, and questionnaires were used to collect data. The data analysis technique was carried out based on the validation analysis results of media and material experts, as well as the module's feasibility according to students. Results: At the research and information gathering stages, the research results were obtained by incorporating material from the previous module on menstruation and sexually deviant behavior, particularly LGBT. The planning stage included application aspects, materials, and usage instructions. With the addition of revised trial results in practice questions and adapted religious materials, the development results show that the module is ready for use.Conclusions: According to the results of the study, the adolescent reproductive health learning module using Artificial Intelligence was appropriate as an educational medium. It is suggested that the press be improved in terms of media display and comprehensive material.